The Antiviral RNAi Response in Vector and Non-vector Cells against Orthobunyaviruses - Dietrich, Isabelle; Shi, Xiaohong; McFarlane, Melanie; Watson, Mick; Blomström, Anne-Lie; Skelton, Jessica K.; Kohl, Alain; Elliott, Richard M.; Schnettler, Esther (PLoS neglected tropical diseases, 2017)
Vector arthropods control arbovirus replication and spread through antiviral innate immune responses including RNA interference (RNAi) pathways. Arbovirus infections have been shown to induce the exogenous small interfering RNA (siRNA) and Piwi-interacting RNA (piRNA) pathways, but direct antiviral activity by these host responses in mosquito cells has only been demonstrated against a limited number of positive-strand RNA arboviruses. For bunyaviruses in general, the relative contribution of small RNA pathways in antiviral defences is unknown. The genus Orthobunyavirus in the Bunyaviridae family harbours a diverse range of mosquito-, midge- and tick-borne arboviruses. We hypothesized that differences in the antiviral RNAi response in vector versus non-vector cells may exist and that could influence viral host range. Using Aedes aegypti-derived mosquito cells, mosquito-borne orthobunyaviruses and midge-borne orthobunyaviruses we showed that bunyavirus infection commonly induced the production of small RNAs and the effects of the small RNA pathways on individual viruses differ in specific vector-arbovirus interactions. These findings have important implications for our understanding of antiviral RNAi pathways and orthobunyavirus-vector interactions and tropism.